Gingival recession coverage by lateral pedicle graft procedure: Case report - Sheoran, Kirtika; Pardeep, Singh; Gyanander, Attresh (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
The coverage of denuded roots represents one of the challenges of periodontal treatment as clinician is not only required to treat disease and improve function but also cope with ever demanding esthetics of patients. Among the several techniques for recession coverage  is the laterally positioned flap. The main advantages of the laterally positioned pedicle graft are that it is relatively easy and not time-consuming, it produces excellent esthetic results and no second surgical site is involved for donor harvesting. This article puts an emphasis on case report in which lateral pedicle graft technique has been used for root coverage of right mandibular central incisor